Śrīgajānana-darśana : Śegāvacyā Śrīgajānana Mahārājāñce bhāvaramya prāsādika caritra - Kher, Bhalchandra Dattatraya, 1917- (Jayaśrī Prakāśana : pramukha vitaraka, Mêjesṭika Buka Sṭôla, 1978)
Biography of Gajanan Maharaj, fl. 1878-1910, saint of Shegaon, Maharashtra.